2019
DOI: 10.1177/0272431619858417
|View full text |Cite
|
Sign up to set email alerts
|

Depressive Symptoms and Achievement Goals: Parental Rejection as a Moderator

Abstract: This present study investigated the longitudinal relations between depressive symptoms and achievement goals and whether maternal and paternal rejection moderated these relations. A sample of 436 early adolescents ([Formula: see text]age = 13.19, 58.33% girls) filled in scales measuring the depressive symptoms (Time 1), parental rejection (Time 2; 1 year later), and achievement goals (Time 2). Early adolescents’ depressive symptoms were positively related to performance-avoidance goals and negatively related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 83 publications
(138 reference statements)
0
7
0
1
Order By: Relevance
“…In early adolescents, depression symptoms were found to be negatively associated with mastery goals but unrelated to performance goals (Sideridis, 2005). However, research across an entire school year found that students’ depression symptoms predicted decreases in mastery and performance-approach goals, and increases in performance-avoidance goals (Măirean & Diaconu-Gherasim, 2020). Among high school students, depression was found to be positively associated with both performance-approach and avoidance goals (Mastrotheodoros et al, 2017).…”
Section: Internalized Symptoms and Achievement Goalsmentioning
confidence: 99%
See 1 more Smart Citation
“…In early adolescents, depression symptoms were found to be negatively associated with mastery goals but unrelated to performance goals (Sideridis, 2005). However, research across an entire school year found that students’ depression symptoms predicted decreases in mastery and performance-approach goals, and increases in performance-avoidance goals (Măirean & Diaconu-Gherasim, 2020). Among high school students, depression was found to be positively associated with both performance-approach and avoidance goals (Mastrotheodoros et al, 2017).…”
Section: Internalized Symptoms and Achievement Goalsmentioning
confidence: 99%
“…Researchers have focused on individual and contextual factors that can predict these developmental trajectories, such as gender (Theis & Fischer, 2017) or teachers’ supportive practices (Ciani et al, 2011; Mouratidis et al, 2018). Some studies found relationships between personal attributes, including neuroticism (′Vaulerin et al, 2016), fear of failure (Bartels & Magun-Jackson, 2009; Elliot & Church, 1997), as well as with depression and anxiety symptoms (Ariani, 2017; Măirean & Diaconu-Gherasim, 2020; Mastrotheodoros et al, 2017; Sideridis, 2005). Yet, little is known on the specific role of depression and anxiety symptoms in the development of achievement goals over long periods of time.…”
mentioning
confidence: 99%
“…Além dos EIDs outras variáveis foram relacionadas à autolesão nos estudos encontrados, tais como a presença de sintomas depressivos, transtornos alimentares, rejeição parental, ruminação e traços de personalidade. Os sintomas depressivos, a rejeição parental e a ruminação estão tanto associados entre si (Carnevali, Thayer, Brosschot, & Ottaviani, 2018;Măirean & Diaconu-Gherasim, 2020), quanto aos EIDs (Haugh, Miceli, & DeLorme, 2017), aos traços de neuroticismo (Roelofs, Huibers, Peeters, & Arntz, 2008) e à autolesão (Tilton-Weaver, Marshall, & Svensson, 2019; Zhu, Chen, & Su, 2020). Teoricamente, os eventos nocivos precoces como os provocados pela rejeição parental atuam junto com alguns temperamentos (e traços de personalidade) contribuindo para o desenvolvimento de EIDs, tornando o indivíduo vulnerável às autolesões, à ruminação e aos sintomas depressivos.…”
Section: Variáveis Relacionadas a Autolesão E Eidsunclassified
“…Finally, Diaconu-Gherasim, and Mairean (2020) looked at longitudinal links between depressive symptoms and achievement goals, and whether rejection by mothers and fathers had an impact on these links in a Romanian sample of early adolescents. The results showed a positive link between depressive symptoms and performance-avoidance goals, but a negative link to both mastery and performance-approach goals.…”
Section: New Insights From This Special Issuementioning
confidence: 99%